Runoff from upstream changes the structure and energy flow of food web in estuary - Yi, Yujun; Zhao, Fanxuan; Liu, Qi; Song, Jie (Frontiers in Marine Science, 2023)
Introduction Sediment and nutrients flow into estuary with runoff, and then influence the estuary ecosystem. Much work has been done for investigating the response of water quality and species group (eg. phytoplankton or zooplankton) to the runoff from upstream, while few research has been taken to evaluate the response of the whole ecosystem. Methods Food webs of different seasons and regions were established based on stable isotope analysis and Bayesian mixing model. The influences of upstream runoff and sediment transport on the estuarine food webs were analyzed. Results Food web in estuary had highly spatial-temporal variability. The stable isotope values of organisms were higher on the northern shore than that on the southern shore. The area with high-turbidity freshwater inflow nurtured more terrestrial- organic- matter (TOM) relying species. And the contribution of TOM to food web was higher in flood season than that in non-flood season. The trophic levels of major consumers in the non-flood season were generally higher than that in the flood season. Significant differences in the average TP of species between two shores appeared during the non-flood season (P < 0.05). Expect for the C value, all of the topological indexes of food webs on the northern shore were higher than those on the southern shore, and they were higher in the flood period. Discussion The input and diffusion of sediment and nutrients carried by runoff led to the changes in the dietary structure of estuarine organisms and the decrease in trophic levels of major consumers. At the same time, flow pulse with high sediment also aggravated the spatial differences of the structure of food webs. The higher contribution of TOM to consumers increased the link density of food web on the southern shore, making it a more robust system. However, the high diversity of food sources and aquatic species made the food web more complex on the northern shore.